Turbulent heat transfer enhancement in tubular heat exchangers with different twisted tape inserts - S.H. Labib; M. R. A. Himel; J.I. Ali; A.R. Mim; M.J. Hossain; A.K. Ghosh; A. Goswami (Journal of Mechanical Engineering and Sciences, 2021)
Experimental and numerical analyses are carried out to investigate the influence of twisted tape inserts on the heat transfer and the flow behavior in double tube heat exchangers. First, all the performance factors, namely the Nusselt number, friction factor, and thermal performance factor, were studied for a basic heat exchanger (BHE). Afterwards, twisted tapes with three different twist ratios (7.5, 6, and 4.5) were inserted inside the inner tube of the BHE, which resulted in three different modified heat exchangers (MHEs). For the numerical study, a 3D numerical model is developed with the k-ε RNG turbulent model to visualize the flow and the heat transfer behavior inside the heat exchangers. In both studies, turbulent flow field is maintained, ranging Reynolds number from 15000 to 50000. From the experimental result, an enhanced heat transfer, characterized by the performance factors, is found for all the MHEs compared to the BHE. The most enhanced thermal performance factor is achieved for the MHE with the lowest twist ratio. Finally, a good agreement between obtained numerical and experimental results reveals that the present numerical model can reliably predict the flow and heat transfer behavior in double tube heat exchangers.